Bridge over Troubled Water: Patients’ Opportunities for Collective Participation in Substance Use Institutions through Research Circles - Brit-Marie Follevåg (MDPI AG, 2021)
This study explores patients’ opportunities for collective participation in an institution for people with substance use disorder. Patients and staff from the treatment institution cooperated with researchers to make changes in the treatment practice, using a research circle as a model for the project. In the article, we discuss the following research questions: How and in what areas did patients have the opportunity to participate collectively in the treatment institution? How did the patients experience participation in the research circle? Data consist of minutes from meetings, seminars, and focus-group interviews. The participants analysed the material together, and the authors carried out a thematic analysis after the project. The participants chose to explore how milieu therapy could build a bridge from treatment in the institution to life after treatment, a “Bridge over troubled waters”, to quote Simon and Garfunkel. Findings show that activities in the research circle led to changes at the institution, e.g., regular Sunday afternoon meetings, a weekly quiz, and less controlling procedures of substance use, and that the institutional culture in general became based more on participation and equality. Patients, staff, and researchers participated in a partnership; mutual recognition promoted cooperation and fellowship in the research circle. We conclude that the project provided the participants with opportunities for collective participation in the institution. In addition, the patients experienced partnership and empowerment in the research circle. Our attempts to change institutional practices yielded some improvements but also met with structural and cultural barriers. Thus, the project experienced challenges and obstacles mostly related to limitations in the institutional system and culture.